2017
DOI: 10.1002/bab.1518
|View full text |Cite
|
Sign up to set email alerts
|

Detection of exogenous gene doping of IGF‐I by a real‐time quantitative PCR assay

Abstract: Gene doping can be easily concealed since its product is similar to endogenous protein, making its effective detection very challenging. In this study, we selected insulin-like growth factor I (IGF-I) exogenous gene for gene doping detection. First, the synthetic IGF-I gene was subcloned to recombinant adeno-associated virus (rAAV) plasmid to produce recombinant rAAV2/IGF-I-GFP vectors. Second, in an animal model, rAAV2/IGF-I-GFP vectors were injected into the thigh muscle tissue of mice, and then muscle and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…It has been reported that human candidate genes at a high risk of gene doping include EPO , insulin-like growth factor-1 ( IGF-1 ), hypoxia inducible factor-1 ( HIF-1 ), vascular endothelial growth factor-a ( VEGF-A ), and follistatin ( FST ), etc. [20,21,22]. Gene doping may enhance their expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that human candidate genes at a high risk of gene doping include EPO , insulin-like growth factor-1 ( IGF-1 ), hypoxia inducible factor-1 ( HIF-1 ), vascular endothelial growth factor-a ( VEGF-A ), and follistatin ( FST ), etc. [20,21,22]. Gene doping may enhance their expression.…”
Section: Discussionmentioning
confidence: 99%
“…LAMP and PCR-based gene doping detection methods (like real-time PCR, nested PCR, droplet digital PCR and internal threshold PCR) target exon-exon junctions of transgenic gene constructs similarly to our NGS-based method [3,[5][6][7][8][9][10][11][12][13]. However, these methods need at least one wild-type copyDNA junction for detection of gene doping [6,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Currently published methods for detection of gene doping use PCR-based methods or loop-mediated isothermal amplification (LAMP) that target unique sequences in a doping gene corresponding to exon-exon junctions in the intron-less transgene [3,[5][6][7][8][9][10][11][12][13]. However, because the exon-exon junctions of doping genes are known and the short PCR primers are even interrupted by the slightest change of the sequence, it is relatively simple to evade detection using current PCR-based methods by modifying the doping gene with for example synonymous mutations, which will then give a false-negative result.…”
Section: Introductionmentioning
confidence: 99%
“…Although not yet commonplace, research in the eld of gene therapy is constantly improving [34][35][36][37] and with every advancement in genetic methods intended for hereditary disease therapies, comes further opportunities for exploiting the technology for doping strategies [38][39][40][41][42]. Therefore, developing methodologies to combat this is necessary [43][44][45].…”
Section: Introductionmentioning
confidence: 99%